ACID BASE STUDENTS ACTIVITIES SHEETS THROUGH GUIDED DISCOVERY TO PRACTICE SCIENCE LITERACY - Sanny Murti Vinandari (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
Student Activity Sheet (SAS) based on guided discovery learning model is needed to improve students' scientific literacy. The type of research used in this study is research and development (R & D) until the limited testing phase and was conducted to 12 students of 11st grade of SMAN 1 Krian to know the effectiveness of the SAS. The instruments used in this study are the pretest-posttest sheet about students scientific literacy. The SAS stated effective if the posttest result for each domain of scientific literacy get percentage >75% with high or very high category The results showed that effectiveness includes scientific literacy test get high and very high category. From this research, the students scientific literacy has increased from pretest to posttest. The percentage of each domain of scientific literacy are Science Contex about 79,16%; Science Knowledge, Content knowledge about 75%, Procedural knowledge about 91,67%, Epistemic knowledge about 100%; Science Competence about 100%; and Science attitude about 100%.